Diplazium thailandicum (Athyriaceae), a new fern from Thailand - Pongkai, Puttamon; Zhang, Liang; Boonkerd, Thaweesakdi; Pollawatn, Rossarin (Phytotaxa, 2018)
A new fern species, Diplazium thailandicum (Athyriaceae), is described. It was discovered from the North of Thailand. It is distinguished from the most similar species, D. chioui and D. lobatum, in having a pinnatisect base of the terminal pinna, 5–8 pairs of oblong lateral pinnae with stalk < 5 mm, and sori curved, 0.5–0.7 cm long, and borne half way between midribs and margins.